D-penicillamine prevents ram sperm agglutination by reducing the disulphide bonds of a copper-binding sperm protein. Issue 5 (May 2016) - Leahy, T; Rickard, JP; Aitken, RJ; de Graaf, SP
Abstract: Head-to-head agglutination of ram spermatozoa is induced by dilution in the Tyrode's capacitation medium with albumin, lactate and pyruvate (TALP) and ameliorated by the addition of the thiol d-penicillamine (PEN). To better understand the association and disassociation of ram spermatozoa, we investigated the mechanism of action of PEN in perturbing sperm agglutination. PEN acts as a chelator of heavy metals, an antioxidant and a reducing agent. Chelation is not the main mechanism of action, as the broad-spectrum chelator ethylenediaminetetraacetic acid and the copper-specific chelator bathocuproinedisulfonic acid were inferior anti-agglutination agents compared with PEN. Oxidative stress is also an unlikely mechanism of sperm association, as PEN was significantly more effective in ameliorating agglutination than the antioxidants superoxide dismutase, ascorbic acid, α-tocopherol and catalase. Only the reducing agents cysteine and dl-dithiothreitol displayed similar levels of non-agglutinated spermatozoa at 0 h compared with PEN but were less effective after 3 h of incubation (37 °C). The addition of 10 µM Cu 2+ to 250 µM PEN + TALP caused a rapid reversion of the motile sperm population from a non-agglutinated state to an agglutinated state. Other heavy metals (cobalt, iron, manganese and zinc) did not provoke such a strong response. Together, these results indicate that PEN prevents sperm association by the reduction of disulphide bonds on a sperm membrane protein that binds copper. ADAM proteins are possible candidates, as targeted inhibition of the metalloproteinase domain significantly increased the percentage of motile, non-agglutinated spermatozoa (52.0% ± 7.8) compared with TALP alone (10.6% ± 6.1). Reproduction (2016) 151 1–10